Molecular Study of Vaginal Lactobacillus Acidophilus Carried Bacteriocin Gene and Effect of Different Conditions on the Presence of Lactobacillus in Some Iraq Women - AlMndalawi, Jenan Jafr Baksh (International Journal of Psychosocial Rehabilitation, 2020)
Vaginal Lactobacillus acidophilus has ability to bacteriocins production the greatly broader inhibitory spectra that bacteriocins make and different conditions effect on the presence of vaginal Lactobacillus. Molecular study of vaginal L. acidophilus carried bacteriocin gen and effect of different conditions on the presence of vaginal Lactobacillus. Vaginal swabs of healthy women from hospitals in Baghdad city for isolation of Lactobacillus acidophilus to study effect of different conditions on the presence of vaginal Lactobacillus were inoculated in MRS broth medium, after 24 h incubation in the presence of 5% CO2 the specimens were subcultured on MRS agar, 11 isolates from 49 isolates identified by PCR technique were Lactobacillus acidophilus from total 104 Lactobacillus isolates. The first identification presented (n=49)(22.9%) L. acidophilus isolates then using conventional polymerase chain reaction (PCR) with specific primers gene which showed that (n=11)(22.4%) isolates were Lactobacillus acidophilus carried bacteriocin gene with high molecular weight 4000bp, also 11 L. acidophilus isolates characterized by their ability to inhibit the growth of Pseudomonas aeroginosa, Escherichia coli and Staphylococcus aureus through the production of bacteriocin. This study suggested highly significant difference during Lactobacillus acidophilus (n=11)(22.4%) isolates from (n=49)(22.9) isolates by PCR technique and highly significant difference during studied parameter effect on the presence of vaginal Lactobacillus (Antibiotic intake , hormonal contraceptive,age, intravaginal products for douching, menstruation and breast feeding).